Abnormal Magnetic Signals Characterization of Fatigue Crack Propagation Life. Issue 1 (November 2020) - Shi, Changliang; Zhang, Xin; Lin, Yimin; Guan, Rutao; Yang, Hongyan
Abstract: In this research, the abnormal magnetic signals were detected in dynamic tension tests on the ferromagnetic material specimens, in order to study the characterization method of abnormal magnetic signals for the crack propagation life. It is indicated that fatigue crack length a is linear with the peak-peak value ΔHpa (y) of abnormal magnetic signals. The ΔHpa (y) of fatigue crack and the gradient of magnetic field intensity k increase with the increase of fatigue cycle number. Therefore, ΔHpa (y) and k are confirmed as the key parameters of characterizing crack propagation life. Then, a life prediction model of abnormal magnetic signals for the crack propagation life is founded based on the Paris equation. The maximum error between measured values and calculated values is less than 15%.